Near-infrared fluorescence imaging of hepatocellular carcinoma cells regulated by β-catenin signaling pathway - Song, Jian; Ren, Tingting; Duan, Yanheng; Guo, Haitao; Wang, Gang; Gan, Yu; Bai, Mengcai; Dong, Xiaotian; Zhao, Zheng; An, Jiaze (Frontiers in Oncology, 2023)
Near-infrared fluorescence (NIRF) imaging has recently emerged as a promising tool for noninvasive cancer imaging. However, lack of tumor sensitivity and specificity restricts the application of NIRF dyes in surgical navigation. Here we demonstrated that NIRF dye MHI-148 was biocompatible as indocyanine green (ICG) but with higher imaging intensity and preferential uptake and retention in hepatocellular carcinoma (HCC) cells and tissues. Moreover, our data indicated that membrane transporters OATP2B1 and ABCG2, which regulated by β-catenin signaling pathway, mediated tumor-specific accumulation and retention of MHI-148 in HCC cells. In addition, the treatment with β-catenin inhibitor significantly enhanced the accumulation of MHI-148 in HCC tissues and improved the efficacy of tumor imaging with MHI-148 in vivo. Our study uncovers a mechanism that links the distribution and expression of the membrane transporters OATP2B1 and ABCG2 to the tumor-specific accumulation of MHI-148, and provides evidence supporting a regulating role of the β-catenin signaling pathway in OATP2B1 and ABCG2- induced retention of MHI-148 in HCC tissues. Our findings suggest that strategy targeting key components of MHI-148 transport machinery may be a potential approach to improve HCC imaging.